2001
DOI: 10.1192/pb.25.4.140
|View full text |Cite
|
Sign up to set email alerts
|

Survey of psychotherapy training for psychiatric trainees in South-West England

Abstract: Aims and MethodA telephone questionnaire to assess psychotherapy training in the 12 psychiatric training schemes in South-West England was conducted in April 1999. The findings were compared with the 1993 guidelines recommended by the Royal College of Psychiatrists.ResultsOnly one scheme was achieving the standards set by the College guidelines. The majority of trainees in this region were not receiving adequate psychotherapy training.Clinical ImplicationsPsychotherapy training for psychiatric trainees needs u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…Previous studies have compared the recommendations from 1993 (Grant et al, 1993) with practice (Hamilton & Tracy, 1996;Hwang & Drummond, 1996;Byrne & Meagher, 1997;Rooney & Kelly, 1999;McCrindle et al, 2001;Podlejska-Eyres & Stern, 2003;Carley & Mitchinson, 2006). These studies have recommended improvements in the availability and quality of psychotherapy supervision.…”
mentioning
confidence: 99%
“…Previous studies have compared the recommendations from 1993 (Grant et al, 1993) with practice (Hamilton & Tracy, 1996;Hwang & Drummond, 1996;Byrne & Meagher, 1997;Rooney & Kelly, 1999;McCrindle et al, 2001;Podlejska-Eyres & Stern, 2003;Carley & Mitchinson, 2006). These studies have recommended improvements in the availability and quality of psychotherapy supervision.…”
mentioning
confidence: 99%
“…Although it is mandatory to fulfil these requirements in order to enter for the MRCPsych part II examination, there is evidence from existing literature that senior house officers (SHOs) have often been unable to meet them (McCrindle et al, 2001;Pretorius & Goldbeck, 2006). The aim of this study was to explore the extent to which SHOs were meeting the College psychotherapy requirements.…”
Section: Discussionmentioning
confidence: 99%
“…The Royal College of Psychiatrists produced guidelines in 1993 and again in 2001 outlining the training requirements for basic specialist trainees to have experience in several forms of psychotherapy (Royal College of Psychiatrists, 1993, 2001). There are five basic requirements:…”
Section: Discussionmentioning
confidence: 99%
“…The literature shows that psychiatric trainees generally did not meet the College requirements (Arnott et al, 1993;Hamilton & Tracy, 1996;Hwang & Drummond, 1996;Byrne & Meagher, 1997;Rooney & Kelly, 1999;McCrindle et al, 2001). Podlejska-Eyers & Stern (2003) showed that it was possible to fulfil some of the College requirements even with a relatively understaffed and underresourced service, but did not comment on the proportion of trainees fulfilling all requirements.…”
Section: Discussionmentioning
confidence: 99%